Comparing individual muscle size and strength responses in younger and older adults after prolonged resistance training - Vandeweerd, Joshua (2021)
Several weeks of systematic resistance exercise, termed resistance training (RT), increases muscle size and strength in both younger and older adults and is recognized as a key measure towards combatting age-related neuromuscular decline. Considerable inter-individual variation exists, however, in the adaptations to RT. Whether this inter-individual variation differs between younger and older adults has not been extensively studied. Further, whether baseline characteristics such as pre-training muscle size and strength can predict individual responses to RT is not definitively known. The purpose of this study was to determine the magnitude of inter-individual variability in responses to prolonged RT, whether it differs between younger and older adults, and whether pre-training characteristics are related to an individual’s response to RT.